Systematic Assessment of 10 Biomarker Candidates Focusing on α‐Synuclein‐Related Disorders. Issue 12 (7th August 2021) - Schulz, Isabel; Kruse, Niels; Gera, Roland G.; Kremer, Thomas; Cedarbaum, Jesse; Barbour, Robin; Zago, Wagner; Schade, Sebastian; Otte, Birgit; Bartl, Michael; Hutten, Samantha J.; Trenkwalder, Claudia; et al.
ABSTRACT: Background: Objective diagnostic biomarkers are needed to support a clinical diagnosis. Objectives: To analyze markers in various neurodegenerative disorders to identify diagnostic biomarker candidates for mainly α‐synuclein (aSyn)‐related disorders (ASRD) in serum and/or cerebrospinal fluid (CSF). Methods: Upon initial testing of commercially available kits or published protocols for the quantification of the candidate markers, assays for the following were selected: total and phosphorylated aSyn (pS129aSyn), neurofilament light chain (NfL), phosphorylated neurofilament heavy chain (pNfH), tau protein (tau), ubiquitin C‐terminal hydrolase L1 (UCHL‐1), glial fibrillary acidic protein (GFAP), calcium‐binding protein B (S100B), soluble triggering receptor expressed on myeloid cells 2 (sTREM‐2), and chitinase‐3‐like protein 1 (YKL‐40). The cohort comprised participants with Parkinson's disease (PD, n = 151), multiple system atrophy (MSA, n = 17), dementia with Lewy bodies (DLB, n = 45), tau protein‐related neurodegenerative disorders (n = 80, comprising patients with progressive supranuclear palsy (PSP, n = 38), corticobasal syndrome (CBS, n = 16), Alzheimer's disease (AD, n = 11), and frontotemporal degeneration/amyotrophic lateral sclerosis (FTD/ALS, n = 15), as well as healthy controls (HC, n = 20). Receiver operating curves (ROC) with area under the curves (AUC) are given for each marker. Results: CSF total aSyn was decreased. NfL, pNfH, UCHL‐1, GFAP, S100B, and sTREM‐2 were increased in patients with neurodegenerative disease versus HC ( P < 0.05). As expected, some of the markers were highest in AD (i.e., UCHL‐1, GFAP, S100B, sTREM‐2, YKL‐40). Within ASRD, CSF NfL levels were higher in MSA than PD and DLB ( P < 0.05). Comparing PD to HC, interesting serum markers were S100B (AUC: 0.86), sTREM2 (AUC: 0.87), and NfL (AUC: 0.78). CSF S100B and serum GFAP were highest in DLB. Conclusions: Levels of most marker candidates tested in serum and CSF significantly differed between disease groups and HC. In the stratification of PD versus other tau‐ or aSyn‐related conditions, CSF NfL levels best discriminated PD and MSA. CSF S100B and serum GFAP best discriminated PD and DLB. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society.